EFFECTIVENESS OF THE DETECTIVE GAME OF CHEMISTRY MEDIA ON STUDENTS LEARNING OUTCOMES IN GREEN CHEMISTRY MATERIAL - Agung Wijaya; Muchlis Muchlis (UNESA Journal of Chemical Education, 2026)
This study was motivated by the topic of green chemistry, which requires an understanding of reducing or eliminating the use of hazardous chemicals for humans and the environment; therefore, innovative and engaging learning media are needed. This study aimed to determine the effectiveness of Detective Game of Chemistry in improving students’ learning outcomes on green chemistry topics. The research method used was a quantitative approach with a one-group pretest-posttest design, where the pretest was used to measure students’ initial abilities and the posttest was used to measure learning outcomes after the treatment. Data analysis was conducted using the Wilcoxon Signed Rank Test, classical completeness (mastery learning), and N-gain. The results showed a significance value of 0.001, indicating that there was an improvement in learning outcomes, as posttest scores were higher than pretest scores. The classical completeness result was 96%, categorized as very good and exceeding the success criterion of ≥75%, indicating that the learning process was effective. The N-gain analysis showed that 4% of students were in the low category, 50% in the medium category, and 46% in the high category, with an average N-gain of 0.73, which is classified as high. Based on these results, Detective Game of Chemistry is considered effective in improving students’ learning outcomes in green chemistry using an Android-based learning media.